Interannual variations in surface urban heat island intensity and associated drivers in China. (15th September 2018) - Yao, Rui; Wang, Lunche; Huang, Xin; Zhang, Wenwen; Li, Junli; Niu, Zigeng
Abstract: The spatial, diurnal and seasonal variations of surface urban heat islands (SUHIs) have been investigated in many places, but we still have limited understanding of the interannual variations of SUHIs and associated drivers. In this study, the interannual variations in SUHI intensity (SUHII, derived from MODIS land surface temperature (LST) data (8-day composites of twice-daily observations), urban LST minus rural) and their relationships with climate variability and urbanization were analyzed in 31 cities in China for the period 2001–2015. Significant increasing trends of SUHII were observed in 71.0%, 58.1%, 25.8% and 54.8% the cities in summer days (SDs), summer nights (SNs), winter days (WDs) and winter nights (WNs), respectively. Pearson's correlation analyses were first performed from a temporal perspective, which were different from a spatial perspective as previous studies. The results showed that the SUHII in SDs and WDs was negatively correlated with the background LST and mean air temperature in most of the cities. The nighttime SUHII in most cities was negatively and positively correlated with total precipitation and total sunshine duration, respectively. Average wind speed has little effect on SUHII. Decreasing vegetation and increased population were the main factors that contributed to the increased SUHII in SDs and SNs, while albedo only influenced the SUHII in WDs. In addition, Pearson's correlation analyses across cities showed that cities with higher decreasing rates of vegetation exhibited higher increasing rates of the SUHII in SDs and WDs. Cities with larger population growth rates do not necessarily have higher increasing rates of SUHII. Graphical abstract: The temporal trends of SUHII on SDs in the WUA in 31 cities in China. Image 1 Highlights: The interannual variations in surface urban heat island intensity (SUHII) and their relationships with climate variability and urbanization were analyzed. Decreasing vegetation and increased population in whole urban area were important factors contributing to the increasing SUHII. The impacts of climate variability on SUHII in the city center depended on time periods and geographical positions.